DNA-based visual majority logic gate with one-vote veto function - Fan, Daoqing (Royal Society of Chemistry, 2015)

(untitled) (Chem Sci)
A molecular logic gate is a basic element and plays a key role in molecular computing. Herein, we have developed a label-free and enzyme-free three-input visual majority logic gate which is realized for the first time according to DNA hybridization only, without DNA replacement and enzyme catalysis. Furthermore, a one-vote veto function was integrated into the DNA-based majority logic gate, in which one input has priority over other inputs. The developed system can also implement multiple basic and cascade logic gates.